2016
DOI: 10.1177/0748233716660641
|View full text |Cite
|
Sign up to set email alerts
|

Carbon monoxide poisoning cases presenting with non-specific symptoms

Abstract: Carbon monoxide (CO) is a colourless and odourless gas appearing as a result of incomplete combustion of carbon-containing fuels. Many domestic or occupational poisonings are caused by CO exposure. Malfunctioning heating systems, improperly ventilated motor vehicles, generators, grills, stoves and residential fires may be listed in the common sources of CO exposure. The aim of this study was to emphasize the significance of early diagnosis of CO poisoning with non-invasive measurement of CO levels of the patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 20 publications
0
10
0
2
Order By: Relevance
“…17 Dysrhythmia, T wave abnormalities, and ST segment changes are the most common findings. 18 In a study by Deniz et al 19 in 106 patients, T wave negativity was found in 11.3% of cases, sinus tachycardia in 26.4%, ST change in 10.4%, and normal ECG in the remaining 66%. In a prospective study by Ozyurt et al 20 in 22 patients, prolonged Qtc interval was detected in the group with poisoning compared to the control group but no dysrhythmia was observed.…”
Section: Discussionmentioning
confidence: 96%
“…17 Dysrhythmia, T wave abnormalities, and ST segment changes are the most common findings. 18 In a study by Deniz et al 19 in 106 patients, T wave negativity was found in 11.3% of cases, sinus tachycardia in 26.4%, ST change in 10.4%, and normal ECG in the remaining 66%. In a prospective study by Ozyurt et al 20 in 22 patients, prolonged Qtc interval was detected in the group with poisoning compared to the control group but no dysrhythmia was observed.…”
Section: Discussionmentioning
confidence: 96%
“…Firepots, car engines, and room heaters were sources of CO in this study as well as in other studies. [ 3 4 ] Use of room heaters, which is shown to be one of the top sources of CO fatalities, is predominant during the winter season and can release high amounts of CO if the equipment is not functioning properly or the place is not ventilated. [ 1 ] In this study too, the rooms in which the deceased were sleeping with the firepots/room heater were having poor ventilation with vents sealed to prevent any cold breeze.…”
Section: Discussionmentioning
confidence: 99%
“…[ 2 ] Malfunctioning heating systems, improperly ventilated motor vehicles, generators, grills, stoves, and residential fires may be listed in the common sources of CO exposure. [ 3 4 ]…”
Section: Introductionmentioning
confidence: 99%
“…CO as a colorless, tasteless and odorless gas, produced by carbon or carbonaceous material combust insufficient in oxygen [3,4], is often overlooked by people. It is toxic to multiple organs such as lung, brain, kidney and so on [5].…”
Section: Discussionmentioning
confidence: 99%